Rio, Zona Norte (1957) by Nelson Pereira dos Santos: popular music as representation of a cultural impasse (Per Musi, 2014)
This paper intends to examine a specific type of relationship between cinema and popular music, whose historical trajectory can be located between the 1930s and 1950s, and which expressed the attempt to build a popular type of film that was the expression of a Brazilian national identity. In many films of this period, popular music not only played a functional or ornamental role in the narrative, but it was also themed as a “representation” of social, aesthetic and ideological dilemmas connected with “Brazilianness”, as seen by the political left, especially the left connected with the Brazilian Communist Party.